The importance of HIV / AIDS in the world of work - de La Rosa Bedriñana, Mariem Vicky (2008)
The following article analyzes the consequences that HIV/ AIDS disease has in the workplace as well as the importance of implementing a suitable labor legislation in order to eradicate discrimination acts of against those affected within the workplace.